Weather-resistant sealant for exhaust system

By using a combination of acrylate copolymer and other ingredients, a high-performance exhaust system sealant was prepared, which solved the problem of poor weather resistance of existing sealants under high temperature and high humidity conditions, and achieved high bonding strength and fire resistance Sexual effect.

CN119193049APending Publication Date: 2024-12-27BEIJING LIHAOJIAYUAN BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411312811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing exhaust system sealants have poor weather resistance under high temperature and high humidity conditions, and cannot meet the requirements of weather resistance, adhesion and fire resistance at the same time, resulting in attenuation of sealing performance.

Method used

Use the reasonable combination of emulsions and other components of two acrylate copolymers, including isocyanate prepolymers, epoxy resins, reactive flame retardants and modified calcium carbonate, etc. to prepare seals with high bonding strength and weather resistance. glue.

Benefits of technology

The sealant maintains weather resistance at a high temperature of 900℃, can withstand high temperature and high humidity and salt spray corrosion for a long time, has good bonding strength and sealing effect, and improves fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005051188710000061
    Figure BDA0005051188710000061
Patent Text Reader

Abstract

The invention relates to a weather-resistant sealant for an exhaust system, which is prepared from the following raw materials in parts by mass: 100 parts of emulsion of acrylate copolymer I, 20-30 parts of emulsion of acrylate copolymer II, 7-12 parts of isocyanate prepolymer, 6-10 parts of epoxy resin, 0.5-1 part of curing agent, 20-30 parts of epoxy silane coupling agent modified calcium carbonate and 4-7 parts of reactive flame retardant. 1-2 parts of fumed silica; the acrylate copolymer I is prepared by copolymerizing the following monomers: (methyl) acrylic acid, (methyl) acrylic acid hydroxyl alkyl ester and (methyl) acrylic acid fluorine-containing alkyl ester; the acrylate copolymer II is prepared by copolymerization of the following monomers: (methyl) acrylic acid, (methyl) acrylic acid epoxy ester and tris (2-acryloyloxyethyl) isocyanurate. The weather-resistant sealant for the exhaust system, provided by the invention, can resist high temperature of 900 DEG C after being cured, can resist double 85 high temperature, high humidity and salt spray corrosion experiments for a long time, has very good bonding strength and sealing effect, and can be directly scraped and coated during construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealants, and in particular relates to a weather-resistant sealant for an exhaust system and a preparation method thereof. Background Art

[0002] The exhaust system is a conventional pipeline system for residential and industrial facilities at present, especially the pipeline involving high-temperature flue gas emission. This part of the flue gas is high temperature and contains corrosive components such as sulfur and salt. Some flue gas also carries a large amount of water vapor, which is a high-temperature, high-humidity and highly corrosive gas. Therefore, higher requirements are placed on the sealing of this part of the flue gas. The sealant is required to have excellent weather resistance of high temperature, corrosion resistance, and salt resistance, as well as good sealing performance. It has good adhesion and durability to cement-based, various plastics, glass, metal and its oxidation. In addition, fire resistance needs to be considered, and the sealant is required to have a certain fire resistance level. At present, most civil flues are made of alkali-resistant glass fiber mesh cloth sandwiched in sulphoaluminate cement, while industrial flues are generally made of high-strength glass magnesium flues considering the fire resistance limit. Existing sealants often cannot meet the above-mentioned weather resistance, adhesion, and fire resistance requirements at the same time.

[0003] CN117801685A discloses an exhaust system sealant, which includes a dry material, a refractory material and an admixture, wherein the dry material includes coarse sand, fine sand and cement; and the admixture includes a hydrophobic agent, a dispersant, a redispersible latex powder, a defoamer, a modified hydroxyethyl cellulose ether and wood fiber. However, the sealant has poor weather resistance, and the sealing performance deteriorates especially under high temperature and high humidity conditions. Therefore, it is necessary to develop a high-performance exhaust system sealant. Summary of the invention

[0004] In order to solve the problem that the existing exhaust duct system sealants cannot meet the actual needs, especially for high temperature, high humidity, and corrosive flue gas, the sealing performance decays quickly, the present invention proposes a weather-resistant exhaust system sealant, which achieves both high bonding strength and weather resistance through the emulsion of two acrylic copolymers and reasonable matching of other components. Specifically, the present invention provides the following technical solutions to solve the above technical problems:

[0005] A weather-resistant sealant for exhaust systems comprises the following raw materials in parts by mass: 100 parts of an emulsion of an acrylate copolymer I, 20-30 parts of an emulsion of an acrylate copolymer II, 7-12 parts of an isocyanate prepolymer, 6-10 parts of an epoxy resin, 0.5-1 part of a curing agent, 20-30 parts of epoxysilane coupling agent-modified calcium carbonate, 4-7 parts of a reactive flame retardant, and 1-2 parts of fumed silica; the acrylate copolymer I is prepared by copolymerizing the following monomers: (meth)acrylic acid, (meth)acrylic acid hydroxyalkyl ester, and (meth)acrylic acid fluorinated alkyl ester; the acrylate copolymer II is prepared by copolymerizing the following monomers: (meth)acrylic acid, (meth)acrylic acid epoxy ester, and tris(2-acryloyloxyethyl)isocyanurate.

[0006] Furthermore, the solid contents of the emulsion of the acrylate copolymer I and the emulsion of the acrylate copolymer II are independently 20-30 wt %, such as 25%, 26%, 27%, 28%, 29%.

[0007] Furthermore, in the preparation of acrylate copolymer I, the mass ratio of (meth)acrylic acid, (meth) hydroxyalkyl acrylate and (meth) fluorinated alkyl ester is 30-50:20-30:10-14; in the preparation of acrylate copolymer II, the mass ratio of (meth)acrylic acid, (meth) epoxy acrylate and tris(2-acryloyloxyethyl)isocyanurate is 20-30:10-15:0.2-0.4.

[0008] Furthermore, in the preparation of the emulsion of acrylate copolymer I and the emulsion of acrylate copolymer II, water 2-4 times the total weight of the monomers, a surfactant 10-15wt% of the total weight of the monomers, and an initiator 1-2wt% of the total weight of the monomers are added; the surfactant is selected from sodium long-chain alkylbenzene sulfonate, sodium long-chain alkyl sulfonate, such as SDS; the initiator is a persulfate, such as at least one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0009] Furthermore, the hydroxyalkyl (meth)acrylate is selected from at least one of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; the fluorinated alkyl (meth)acrylate is selected from at least one of trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, and pentafluoropropyl (meth)acrylate; and the epoxy (meth)acrylate is glycidyl (meth)acrylate.

[0010] The inventors did not expect that the above two acrylate copolymers can significantly improve the weather resistance and high temperature resistance of the sealant while maintaining good bonding strength, and can also improve the fire resistance of the sealant. If all monomers are copolymerized together, the resulting copolymer emulsion cannot achieve this effect.

[0011] Furthermore, the isocyanate prepolymer is a polyisocyanate and a small molecule polyol, and a terminal hydroxyl silicone oil react in an inert atmosphere, in the presence of a catalyst and at a first heating temperature. When the isocyanate group (-NCO) of the detection system no longer changes, the reaction is cooled, an imidazole blocking agent is added, the temperature is raised to a second heating temperature, and the reaction is performed to obtain an isocyanate prepolymer; further, the catalyst is an organic tin catalyst, such as at least one of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dioctyltin diacetate, stannous octoate, and stannous isooctanoate, and the catalyst dosage is 1-2wt% of the mass of the polyisocyanate; the first heating temperature is 50-70°C, the reaction time is 5-10h, and the NCO group of the detection system no longer changes; the second heating temperature is 90-110°C, and the reaction time is 2-4h.

[0012] Furthermore, the polyisocyanate is selected from at least one of 2,4-tolyl diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,6-hexyl isocyanate, and isophorone diisocyanate; the small molecule polyol is at least one of glycerol, propylene glycol, ethylene glycol, trihydroxymethylpropane, and pentaerythritol; the number average molecular weight of the terminal hydroxyl silicone oil is 1000-2000; the molar ratio of the NCO group of the polyisocyanate to the hydroxyl group of the small molecule polyol is 1:0.8-0.9; and the mass ratio of the small molecule polyol to the terminal hydroxyl silicone oil is 3-5:1.

[0013] Furthermore, the imidazole blocking agent is selected from at least one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-ethylimidazole, and 3,5-dimethylimidazole, and the amount of the imidazole blocking agent is 0.15-0.2 times the molar amount of the polyisocyanate.

[0014] Furthermore, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin, and the epoxy value is 0.3-0.45.

[0015] Furthermore, the curing agent is selected from at least one of dicyandiamide, 4',4-diaminodiphenyl sulfone and 3',3-diaminodiphenyl sulfone.

[0016] Furthermore, the reactive flame retardant is selected from at least one of hydroxyl-modified DOPO, carboxyl-modified DOPO, and epoxy-modified DOPO. Preferably, it is hydroxyl-modified DOPO, such as at least one of DOPO-BQ (CAS No.: 947342-47-4) and DOPO-HQ (CAS No.: 99208-50-1). Hydroxyl-modified DOPO contains active hydroxyl groups, which can participate in the curing reaction. After curing, it is chemically bonded to the resin in the resin matrix, providing a more reliable flame retardant effect.

[0017] Further, the epoxysilane coupling agent modified calcium carbonate is obtained by modifying calcium carbonate with an epoxysilane coupling agent, and the amount of the epoxysilane coupling agent is 5-10wt% of the mass of the calcium carbonate. The preparation of silane coupling agent modified calcium carbonate is well known in the art. In a specific embodiment of the present invention, calcium carbonate is ultrasonically dispersed in a 70-80% ethanol aqueous solution, an epoxysilane coupling agent is added, heated to reflux for 3-5h, washed with ethanol, and vacuum dried to obtain the obtained calcium carbonate; the epoxysilane coupling agent is selected from at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, and 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane.

[0018] Furthermore, the weather-resistant exhaust system sealant also includes some common auxiliary materials in the art, such as antioxidants, plasticizers, thickeners, etc. The types and amounts thereof are well known in the art, such as 0.1-3 parts of antioxidants, the antioxidants are selected from at least one of antioxidants 1010, antioxidants 1076, antioxidants 168, and antioxidants 1222, 1-10 parts of plasticizers, the plasticizers are selected from at least one of butylene phthalate, dioctyl phthalate, and dioctyl sebacate; 0.1-5 parts of thickeners, the thickeners are selected from hydroxyethyl cellulose.

[0019] The weather-resistant exhaust system sealant provided by the present invention can withstand a high temperature of 900°C after being cured, can withstand long-term double 85 high temperature and high humidity and salt spray corrosion experiments, has good bonding strength and sealing effect, and can be directly scraped and applied during construction. DETAILED DESCRIPTION

[0020] The technical scheme and technical effects of the present invention are further explained below in the form of specific embodiments.

[0021] Example 1

[0022] (S1) Preparation of an emulsion of acrylic acid ester copolymer I: Under a nitrogen atmosphere, monomers of methacrylic acid, hydroxyethyl acrylate and trifluoroethyl methacrylate were added in a mass ratio of 50:30:10 to 2.7 times the mass of water, and 15 wt% of the total mass of the monomers was added as a surfactant SDS, and the mixture was stirred for pre-emulsification. The mixture was heated to 50° C. in a water bath, and 2 wt% of the total mass of the monomers as an initiator ammonium persulfate was slowly added, and the reaction temperature was controlled at 60-70° C. to continue the reaction for 5 h. After cooling, the pH was adjusted to neutral with sodium bicarbonate, and the solid content was adjusted to 25%, to obtain an emulsion I;

[0023] (S2) Preparation of an emulsion of an acrylic ester copolymer II: Under a nitrogen atmosphere, monomers of methacrylic acid, glycidyl methacrylate, and tri(2-acryloyloxyethyl)isocyanurate were added in a mass ratio of 30:10:0.2 into water three times the mass of the monomers, 12 wt% of the total mass of the monomers was added as a surfactant SDS, and the mixture was stirred for pre-emulsification. The mixture was heated to 50° C. in a water bath, and 2 wt% of the total mass of the monomers as an initiator, ammonium persulfate, was slowly added. The reaction temperature was controlled at 60-70° C. and the reaction was continued for 5 h. After cooling, the pH was adjusted to neutral with sodium bicarbonate, and the solid content was adjusted to 25% to obtain an emulsion II.

[0024] (S3) Preparation of modified calcium carbonate: 10 parts by mass of calcium carbonate were ultrasonically dispersed in a 70% ethanol aqueous solution, 1 part by mass of 3-glycidyloxypropyltrimethoxysilane was added, the mixture was heated under reflux for 3 h, washed with ethanol, and dried under vacuum to obtain modified calcium carbonate;

[0025] (S4) Preparation of isocyanate prepolymer: Under nitrogen atmosphere, 17.4 parts by mass of 2,4-tolyl diisocyanate, 80.5 parts by mass of trihydroxymethylpropane (the ratio of NCO of 2,4-tolyl diisocyanate to OH of trihydroxymethylpropane = 1:0.9) and 26.9 parts by mass of terminal hydroxyl silicone oil (number average molecular weight 1200) were added to a reaction kettle, 300 parts by mass of butyl acetate were added, the mixture was stirred and heated to 70°C, and the reaction was kept warm for 6 hours. At this time, the NCO content of the system no longer changed. After cooling, 22 parts by mass of 2-ethyl-4-methylimidazole was added, the temperature was raised to 110°C, the reaction was continued for 3 hours, and the mixture was spin-dried and discharged to obtain an isocyanate prepolymer;

[0026] (S5) 100 parts by mass of emulsion I, 27 parts by mass of emulsion II, 10 parts by mass of isocyanate prepolymer obtained in step (S4), 8 parts of bisphenol A epoxy resin E41, 0.5 parts of dicyandiamide curing agent, 7 parts of DOPO-HQ, 2 parts of meteorological silica, 0.4 parts of antioxidant 1010, 2 parts of plasticizer butyl phthalate, and 1.7 parts of thickener hydroxyethyl cellulose are mixed evenly in a high-speed mixer, and 25 parts by mass of modified calcium carbonate obtained in step (S3) are added, mixed evenly, and vacuum degassed to obtain a sealant.

[0027] Example 2

[0028] The other conditions and operations are the same as those in Example 1, except that in step (S5), the amounts of each material are changed to: 100 parts by mass of emulsion I, 20 parts by mass of emulsion II, 7 parts by mass of isocyanate prepolymer prepared in step (S4), 10 parts of bisphenol A epoxy resin E41, 1 part of dicyandiamide curing agent, 6 parts of DOPO-HQ, 1 part of meteorological silica, 0.5 parts of antioxidant 1010, 1 part of plasticizer butyl phthalate, and 1.5 parts of thickener hydroxyethyl cellulose.

[0029] Example 3

[0030] The other conditions and operations are the same as those in Example 1, except that in step (S5), the amounts of each material are changed to: 100 parts by mass of emulsion I, 30 parts by mass of emulsion II, 12 parts by mass of isocyanate prepolymer prepared in step (S4), 6 parts of bisphenol A epoxy resin E41, 0.5 parts of dicyandiamide curing agent, 5 parts of DOPO-HQ, 1 part of meteorological silica, 0.6 parts of antioxidant 1010, 1.2 parts of plasticizer butyl phthalate, and 1.3 parts of thickener hydroxyethyl cellulose.

[0031] Example 4

[0032] Other conditions and operations are the same as those in Example 1, except that in step (S1), the mass ratio of methacrylic acid, hydroxyethyl acrylate, and trifluoroethyl methacrylate is 30:10:14; in step (S2), the mass ratio of methacrylic acid, glycidyl methacrylate, and tri(2-acryloyloxyethyl) isocyanurate is 20:15:0.4.

[0033] Comparative Example 1

[0034] Other conditions and operations are the same as those in Example 1, except that in step (S1), hydroxyethyl acrylate is not added.

[0035] Comparative Example 2

[0036] Other conditions and operations are the same as those in Example 1, except that in step (S2), tris(2-acryloyloxyethyl)isocyanurate is not added.

[0037] Comparative Example 3

[0038] (S1) Preparation of acrylic copolymer solution: Under nitrogen atmosphere, monomers methacrylic acid, hydroxyethyl acrylate, trifluoroethyl methacrylate, glycidyl methacrylate, and tri(2-acryloyloxyethyl)isocyanurate are added in a mass ratio of 80:30:10:10:0.2 into 2.7 times the mass of water, and 15 wt% of the total mass of the monomers as surfactant SDS is added. The mixture is stirred for pre-emulsification, and the mixture is heated to 50° C. in a water bath. An initiator ammonium persulfate is slowly added in an amount of 2 wt% of the total mass of the monomers, and the reaction temperature is controlled at 60-70° C. to continue the reaction for 5 h. After cooling, the pH is adjusted to neutral with sodium bicarbonate, and the solid content is adjusted to 25% to obtain emulsion III.

[0039] The preparation of modified calcium carbonate is the same as step (S3) of Example 1, and the preparation of isocyanate prepolymer is the same as step (S4) of Example 1.

[0040] 127 parts by mass of emulsion III, 210 parts by mass of isocyanate prepolymer obtained in step (S4), 8 parts of bisphenol A epoxy resin E41, 0.5 parts of dicyandiamide curing agent, 7 parts of DOPO-HQ, 2 parts of meteorological silica, 0.4 parts of antioxidant 1010, 2 parts of plasticizer butyl phthalate, and 1.7 parts of thickener hydroxyethyl cellulose are mixed evenly in a high-speed mixer, and 25 parts by mass of modified calcium carbonate obtained in step (S3) are added, mixed evenly, and vacuum degassed to obtain a sealant.

[0041] Comparative Example 4

[0042] Other conditions and operations were the same as those in Example 1, except that calcium carbonate was used directly without modification.

[0043] Comparative Example 5

[0044] Other conditions and operations are the same as those in Example 1, except that in step (S4), the blocking agent is changed from 2-ethyl-4-methylimidazole to an equimolar amount of methyl ethyl ketone oxime.

[0045] Application Examples

[0046] The sealants of the above embodiments and comparative examples were tested for their performance, and the results are shown in Table 1 below.

[0047] Table 1 Sealant performance test

[0048]

[0049] 1. Dry time : Tested at 25℃ / 60RH%;

[0050] 2. Full curing time : Time to reach maximum shear strength under 60℃ / 60RH% curing conditions.

[0051] 3. Shear Strength , refer to GB / T 7124-2008;

[0052] 4. Flame retardant , refer to GB / T 2408-2021;

[0053] 5. Double 85+ salt spray aging test The conditions were 85°C / 85RH%+5%NaCl+0.05wt% hydrochloric acid acid salt spray, duration 200h.

[0054] 6. Variable temperature cycle One cycle is -20℃ / 2h and 150℃ / 2h.

[0055] 7. High temperature resistance test The temperature was kept at 900℃ for 5h, and the shear strength was tested again after cooling to calculate the shear strength retention rate.

Claims

1. A weather-resistant sealant for exhaust systems, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of an emulsion of an acrylate copolymer I, 20-30 parts of an emulsion of an acrylate copolymer II, 7-12 parts of an isocyanate prepolymer, 6-10 parts of an epoxy resin, 0.5-1 parts of a curing agent, 20-30 parts of epoxysilane coupling agent-modified calcium carbonate, 4-7 parts of a reactive flame retardant, and 1-2 parts of fumed silica; the acrylate copolymer I is prepared by copolymerizing the following monomers: (meth)acrylic acid, (meth)acrylic acid hydroxyalkyl ester, and (meth)acrylic acid fluorinated alkyl ester; the acrylate copolymer II is prepared by copolymerizing the following monomers: (meth)acrylic acid, (meth)acrylic acid epoxy ester, and tris(2-acryloyloxyethyl)isocyanurate.

2. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The solid content of the emulsion of acrylate copolymer I and the emulsion of acrylate copolymer II are independently 20-30 wt %.

3. The weather-resistant exhaust system sealant according to claim 1, characterized in that: In the preparation of acrylate copolymer I, the mass ratio of (meth)acrylic acid, (meth) hydroxyalkyl acrylate and (meth) fluorinated alkyl ester is 30-50:20-30:10-14; in the preparation of acrylate copolymer II, the mass ratio of (meth)acrylic acid, (meth) epoxy acrylate and tris(2-acryloyloxyethyl)isocyanurate is 20-30:10-15:0.2-0.

4.

4. The weather-resistant exhaust system sealant according to claim 3, characterized in that: In the preparation of the emulsion of acrylate copolymer I and the emulsion of acrylate copolymer II, water 2-4 times the total weight of the monomers, a surfactant 10-15wt% of the total weight of the monomers, and an initiator 1-2wt% of the total weight of the monomers are added; the surfactant is selected from sodium long-chain alkylbenzene sulfonate and sodium long-chain alkyl sulfonate; and the initiator is persulfate.

5. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The hydroxyalkyl (meth)acrylate is selected from at least one of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; the fluorinated alkyl (meth)acrylate is selected from at least one of trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, and pentafluoropropyl (meth)acrylate; and the epoxy (meth)acrylate is glycidyl (meth)acrylate.

6. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The isocyanate prepolymer is a polyisocyanate, a small molecule polyol, and a terminal hydroxyl silicone oil reacting in an inert atmosphere, in the presence of a catalyst and at a first heating temperature. When the isocyanate group (-NCO) of the detection system no longer changes, cooling is performed, an imidazole blocking agent is added, the temperature is raised to a second heating temperature, and the reaction is performed to obtain an isocyanate prepolymer; Furthermore, the catalyst is an organic tin catalyst, such as at least one of dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dioctyltin diacetate, stannous octoate, and stannous isooctanoate, and the amount of the catalyst is 1-2wt% of the mass of the polyisocyanate; the first heating temperature is 50-70°C, the reaction time is 5-10h, and the NCO group of the detection system no longer changes; the second heating temperature is 90-110°C, and the reaction time is 2-4h.

7. The weather-resistant exhaust system sealant according to claim 6, characterized in that: The polyisocyanate is selected from at least one of 2,4-tolyl diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, 1,6-hexyl isocyanate, and isophorone diisocyanate; the small molecule polyol is at least one of glycerol, propylene glycol, ethylene glycol, trihydroxymethyl propane, and pentaerythritol; the number average molecular weight of the terminal hydroxyl silicone oil is 1000-2000; the molar ratio of the NCO group of the polyisocyanate to the hydroxyl group of the small molecule polyol is 1:0.8-0.9; the mass ratio of the small molecule polyol to the terminal hydroxyl silicone oil is 3-5:1; Furthermore, the imidazole blocking agent is selected from at least one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-ethylimidazole, and 3,5-dimethylimidazole, and the amount of the imidazole blocking agent is 0.15-0.2 times the molar amount of the polyisocyanate.

8. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin, and the epoxy value is 0.3-0.45; and / or The curing agent is selected from at least one of dicyandiamide, 4',4-diaminodiphenyl sulfone and 3',3-diaminodiphenyl sulfone; and / or The reactive flame retardant is selected from at least one of hydroxyl-modified DOPO, carboxyl-modified DOPO, and epoxy-modified DOPO; preferably hydroxyl-modified DOPO, such as at least one of DOPO-BQ (CAS No.: 947342-47-4) and DOPO-HQ (CAS No.: 99208-50-1).

9. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The epoxysilane coupling agent modified calcium carbonate is obtained by modifying calcium carbonate with an epoxysilane coupling agent, and the amount of the epoxysilane coupling agent is 5-10wt% of the mass of the calcium carbonate; preferably, the epoxysilane coupling agent is selected from at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, and 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane.

10. The weather-resistant exhaust system sealant according to claim 1, characterized in that: The weather-resistant exhaust system sealant also includes auxiliary materials, and the auxiliary materials are selected from at least one of antioxidants, plasticizers, and thickeners.